2008
DOI: 10.1098/rstb.2008.0040
|View full text |Cite
|
Sign up to set email alerts
|

The origin and evolution of a unisexual hybrid:Poecilia formosa

Abstract: Clonal reproduction in vertebrates can always be traced back to hybridization events as all known unisexual vertebrates are hybrids between recognized species or genetically defined races. Interestingly, clonal vertebrates often also rely on interspecific matings for their reproduction because gynogenesis (sperm-dependent parthenogenesis) and hybridogenesis are common modes of propagation. While in most cases these hybridization events leave no hereditary traces in the offspring, occasionally the genome exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 100 publications
(159 reference statements)
5
97
0
1
Order By: Relevance
“…40,41), this state could represent "frozen" heterozygosity in a particularly adaptive genotype, such as seen in unisexual hybrid vertebrates (42).…”
Section: Significancementioning
confidence: 99%
“…40,41), this state could represent "frozen" heterozygosity in a particularly adaptive genotype, such as seen in unisexual hybrid vertebrates (42).…”
Section: Significancementioning
confidence: 99%
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their long history, unisexual species in vertebrates also have large ranges of geographical distribution [8,9,21]. Therefore, 2 basic biological puzzles, i.e.…”
Section: Special Topicmentioning
confidence: 99%
“…Since a unisexual fish, the Amazon molly Poecilia formosa, was first found in 1932 [4], about 80 unisexual complexes that are composed of all-female individuals have been reported in primitive vertebrates [5]. These unisexual species have been demonstrated to reproduce by gynogenesis, hybridogenesis or parthenogenesis, and have long been a major puzzle in evolutionary genetics and ecology [1-3, [6][7][8][9]. Owing to the absence of genetic recombination and the accumulation of deleterious mutations, the unisexual species were generally thought to be short-lived on an evolutionary timescale because of Muller's ratchet [10,11].…”
mentioning
confidence: 99%